2021
DOI: 10.3390/v13091801
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Spread of a B.1.1.28-Derived P.6 Lineage with Q675H and Q677H Spike Mutations in Uruguay

Abstract: Uruguay controlled the viral dissemination during the first nine months of the SARS-CoV-2 pandemic. Unfortunately, towards the end of 2020, the number of daily new cases exponentially increased. Herein, we analyzed the country-wide genetic diversity of SARS-CoV-2 between November 2020 and April 2021. We identified that the most prevalent viral variant during the first epidemic wave in Uruguay (December 2020–February 2021) was a B.1.1.28 sublineage carrying Spike mutations Q675H + Q677H, now designated as P.6, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…No significant association was found between lineages and COVID-19 presentation, even if a lower number of moderate/severe cases were found during alpha-clade epidemic (Table 1). In line with this, patients involved in clusters of B.1.1.7 frequently reported only mild symptoms (moderate/sever infection was detected only in one in-cluster case), and no new amino acid mutation was detected in spike or nucleocapsid proteins, both implicated in SARS-CoV-2 virulence and pathogenicity 31,32,35,36 . B.1.1.7 variant was also found negatively associated with hospitalization in our multivariate model (Table 3).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…No significant association was found between lineages and COVID-19 presentation, even if a lower number of moderate/severe cases were found during alpha-clade epidemic (Table 1). In line with this, patients involved in clusters of B.1.1.7 frequently reported only mild symptoms (moderate/sever infection was detected only in one in-cluster case), and no new amino acid mutation was detected in spike or nucleocapsid proteins, both implicated in SARS-CoV-2 virulence and pathogenicity 31,32,35,36 . B.1.1.7 variant was also found negatively associated with hospitalization in our multivariate model (Table 3).…”
Section: Discussionsupporting
confidence: 60%
“…While clusters of alpha clade involved 17.3% of total B.1.1.7 sequences and did not report evidences of genetic alterations able to increase transmission or pathogenicity, transmission chains of delta clade involved the 28.1% of delta sequences. Thirteen of them reported the Q677H mutation known to enhance viral infectivity and neutralizing antibodies resistance 35,36 . The rapid mechanism of delta clade adaptation, and its onward transmission in local paediatric population might explain its outcompeting and dominance respect pre-and co-existing lineages as P.1 and B.1.1.7, as previously observed in adult population 43 Differently by alpha and delta clade, a limited spread of gamma clade was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether these variants have been observed in other studies; GISAID data revealed that one mutation, Spike (S) Q675H, has previously been observed, present at as much as 3% frequency worldwide (January 2021). This mutation was not circulating at the time that this subject contracted SARS-CoV-2, but has since emerged in multiple SARS-CoV-2 lineages, indicating convergent evolution 32,33 . This mutation falls directly upstream of the furin-cleavage site and is predicted to enhance viral entry 32,33 .…”
Section: Comparison Of Viral Genomic Features Within Subjectsmentioning
confidence: 98%
“…This mutation was not circulating at the time that this subject contracted SARS-CoV-2, but has since emerged in multiple SARS-CoV-2 lineages, indicating convergent evolution 32,33 . This mutation falls directly upstream of the furin-cleavage site and is predicted to enhance viral entry 32,33 . This suggests that this was a functionally advantageous mutation for either infecting the heart specifically, or it may have been broadly advantageous, but did not spread to other tissues because the infection was compartmentalized.…”
Section: Comparison Of Viral Genomic Features Within Subjectsmentioning
confidence: 98%